2019
DOI: 10.1111/jam.14293
|View full text |Cite
|
Sign up to set email alerts
|

Protein profiling of metal‐resistantBacillus cereusVITSH1

Abstract: Aims The aim of the study was to investigate the proteomic changes and antioxidant enzyme activity in chromium‐resistant Bacillus cereus VITSH1 in response to heavy metal toxicity. Methods and Results The variation in protein expression and antioxidant enzyme activity in the presence and absence of metal was studied in B. cereus VITSH1. The differentially expressed proteins in chromium‐treated conditions were determined by SDS PAGE. The proteins involved in metal binding, protein biosynthesis, protein folding,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…The maximum tolerable concentration of the organism to chromium was 2000 mg l −1 (Matilda et al . 2019) and was used in the present study for all the experiments. An overnight culture of the organism was inoculated in nutrient broth pH 7 ± 0·2 containing 2000 mg l −1 chromium and incubated at 100 rev min −1 at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum tolerable concentration of the organism to chromium was 2000 mg l −1 (Matilda et al . 2019) and was used in the present study for all the experiments. An overnight culture of the organism was inoculated in nutrient broth pH 7 ± 0·2 containing 2000 mg l −1 chromium and incubated at 100 rev min −1 at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…An earlier study with a chromium‐resistant Bacillus cereus VITSH1 strain was shown to combat metal stress through the expression of proteins with different functions (Matilda et al . 2019), S layer protein is one such protein known to possess metal‐binding property (Pollmann et al . 2006) expressed by B. cereus VITSH1 on exposure to chromium (Matilda et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein profile was studied after extraction of the protein from bacterial culture using PBS buffer and then quantification was carried out using Bradford assay. Further the characterization and identification of proteins was carried out using SDS page and 2D Gel electrophoresis followed by MALDI-TOF-MS [37][38][39].…”
Section: Identification Of Stress Proteins In the Presence Of Heavy M...mentioning
confidence: 99%
“…Usually, genome analysis is carried out to identify the mechanisms involved in metal resistance and reveal the genes that play an essential role in driving resistance towards particular metals. Whole-genome sequence analysis led to the discovery of several metal resistance genes in a variety of bacterial strains like Bacillus cereus VITSH1for Chromium resistance [11], Pseudomonas aeruginosa FZ-2 for mercury resistance [12], Rhodobacter sp. for Nickel and Copper resistance, Arthrobacter sp.…”
Section: Introductionmentioning
confidence: 99%